Performance Comparison of Various Textile Composition and Structure Through Full-Wave Electromagnetic Simulation and Measurement - Nordin, M.S.Amin; Rahman, N.H.A.; Ali, M.T.; Ahmad Shah, A.A.Sharatol; Ahmad, M.R. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper presents the performance of microstrip patch antenna integrated with textile as a substrate, designed for wearable application. Comparative study between cotton fabric as a substrate with copper tape as radiating element and FR-4 as a substrate with E-textile as a radiating element is performed to evaluate the performance of antennas. The antennas integrated in the proposed structures operate at resonant frequency of 5 GHz. Parameters such as fabric thickness and dielectric permittivity are determined through laboratory measurement prior to simulation to ensure accurate analysis and to take into account non-ideal conditions. Preliminary analysis is performed to observe and investigate the characteristics and electromagnetic performance of the antennas when different types of textile are used as the substrate. Antenna prototypes with two different compositions has been fabricated and tested for validation. The fabricated prototypes give good return loss performance which is -27dB at 4.3 GHz resonant frequency for prototype 1 and -22 dB at 4.7 GHz for prototype 2 (e-textile). However, the frequency for Prototype 2 (E-textile) is slightly shifted about 30% to the left due to non-ideal conditions of the textile materials. The ability of both antennas to radiate good signal is also measured. Based on the measurement data, Prototype 2 (E-textile) shows better performance with higher received power compare to Prototype 1 (copper tape) which is -43 dBm within 1 meter range, while - 58 dBm for Prototype 1.